Penerapan Proyek Penguatan Profil Pelajar Pancasila Tema Gaya Hidup Berkelanjutan Berbasis Pengelolaan Sampah Terhadap Kreativitas Siswa Kelas II SDN Pakis V Surabaya - Yulfa, Okta Indana; Yuliana, Leni; Suryandari, Savitri (Indo-MathEdu Intellectuals Journal, 2025)
The aim of this study is to describe the implementation of the Pancasila student profile strengthening project on the creativity of second-grade students at SDN Pakis V Surabaya, as well as to explore the potential for enhancing student creativity through the Pancasila student profile strengthening project with the theme of sustainable lifestyles. This research adopts a qualitative approach with a descriptive research type. The study was conducted at SDN Pakis V Surabaya, located in the Sawahan sub-district of Surabaya City. The data collected consisted of descriptive information through interviews, observations, and documentation. This study involved 22 students from class II-B of SDN Pakis V Surabaya as subjects. Data analysis was conducted through the procedures of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the implementation of the Pancasila student profile strengthening project, which raises the theme of sustainable lifestyles through waste management in grade II-B of SDN Pakis V Surabaya, has been carried out in a planned and systematic manner. The creativity level of students after participating in this project is in the 'quite creative' category, with an average percentage reaching 67%. Fluency, flexibility, originality, and elaboration are some of the indicators that have been observed, and this indicates that the majority of students are able to come up with their own new ideas.